2019
DOI: 10.1038/s41598-019-48653-9
|View full text |Cite
|
Sign up to set email alerts
|

Allylpyrocatechol, isolated from betel leaf ameliorates thyrotoxicosis in rats by altering thyroid peroxidase and thyrotropin receptors

Abstract: Allylpyrocatechol (APC) was isolated from betel leaf and its possible role in L-thyroxin (L-T 4 )-induced thyrotoxic rats was evaluated. The disease condition, thyrotoxicosis was confirmed by higher levels of thyroid hormones and low thyrotropin (TSH) in serum. Increased hepatic activities of 5′-mono-deiodinase(5′D1), glucose-6-phospatase (G-6-Pase); serum concentrations of alanine transaminase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase(LDH) and tumour necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The obtained data exhibited a notable elevation in the levels of the oxidative stress markers MDA and NO with marked depletion of both non-enzymatic (GSH) and enzymatic (SOD, CAT, and GPx) antioxidants in the hepatic tissues of the hyperthyroid rats due to the prolonged ROS production as well as consumption of the antioxidant defence system components. These results are in line with previous results of Panda et al [ 29 ] and Ashry et al [ 52 ]. Additionally, Kochman et al [ 53 ] reported that the oxidative damage of cellular membrane lipids in hyperthyroid was higher than in euthyroid individuals.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The obtained data exhibited a notable elevation in the levels of the oxidative stress markers MDA and NO with marked depletion of both non-enzymatic (GSH) and enzymatic (SOD, CAT, and GPx) antioxidants in the hepatic tissues of the hyperthyroid rats due to the prolonged ROS production as well as consumption of the antioxidant defence system components. These results are in line with previous results of Panda et al [ 29 ] and Ashry et al [ 52 ]. Additionally, Kochman et al [ 53 ] reported that the oxidative damage of cellular membrane lipids in hyperthyroid was higher than in euthyroid individuals.…”
Section: Discussionsupporting
confidence: 94%
“…(L-thyroxine) to rats along with exposure to a single dose of whole-body γ- radiation resulted in increased levels of both T3 and T4 accompanied by a decrease in the TSH levels in the circulating blood. This uncontrolled excessive release of thyroid hormones resulting from a hyperactive or dysfunctional gland is known as hyperthyroidism or thyrotoxicosis [ 28 , 29 ] which may be attributed to the augmented effect of both Elt. and γ- radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of serum T 3 , T 4 , and TSH in rats were estimated using enzyme‐linked immunosorbent assay method following the instructions attached with each kit, as routinely done in our laboratory. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
“…Based on the analysis of spectral data and compare data with published papers, the compound was identified as 1,2-dihydroxylallylbenzene (Allylpyrocatechol), as shown in Figure 1. 31,32…”
Section: Structural Characterization Of Compoundmentioning
confidence: 99%